HEGEMONI PEMIKIRAN KEAGAMAAN: ETIKA POLITIK DALAM PERSPEKTIF WAHDAH ISLAMIYAH - Dwi Hartini (ASKETIK: JURNAL AGAMA DAN PERUBAHAN SOSIAL, 2019)
This paper attempts to describe the typology model of the Islamic movement that develops in Indonesia which is often classified by the observer, as the typology of moderate Islamic movements, critical idealists, accusatives, Islamic leftists, puritanical Islam, etc. So available typology classifications can help understand the existence of Wahdah Islamiyah’s hegemony of thought. In this case, Wahdah Islamiyah is included in a Puritanism movement, in its development, Wahdah Islamiyah seeks to transform the teachings of purification of Islamic Shariah into socio-political life. Next, to see how Wahdah Islamiyah is with the ideology of revivalism which at first refused to implement the single principle of Pancasila then adapted to the cycle of the political world in Indonesia which applies the single principle of Pancasila. Although it is stated that Wahdah Islamiyah is no longer an exclusive movement, its influence on exclusivity that is still very visible. In this context, Wahdah Islamiyah prefers to be a rational movement.